2002
DOI: 10.1097/00005537-200209000-00020
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gap Junction Uncoupling in the Gerbil Cochlea

Abstract: Gap junctions play a significant role in normal cochlear function. In particular they appear to be essential for maintaining the EP, an activity that could be related to their participation in K+ recycling. Thus, hearing losses associated with mutations in the gene that alter the expression or function of connexin 26 may result from a diminished capacity to recycle K+ from perilymph back to the stria vascularis and a consequent decline in the EP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
7

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 26 publications
1
23
0
7
Order By: Relevance
“…Consistent with this finding, Engel-Yeger et al [2002,2003] detected small OAEs in narrow frequency ranges in homozygotes and compound heterozygotes for the 35delG, W77R, and V37I mutations. Spiess et al [2002] found that uncoupling gap junctions in the Mongolian gerbil inner ear leads to large decreases in OAE magnitudes, but the OAEs, particularly in the low frequencies, do not disappear completely. Also, studies of mice lacking connexin 26 in the inner ear epithelial gap junction network suggest that the cochlear hair cells develop normally in utero, then many, but not all, begin to die postnatally [Cohen-Salmon et al, 2002].…”
Section: Discussionmentioning
confidence: 92%
“…Consistent with this finding, Engel-Yeger et al [2002,2003] detected small OAEs in narrow frequency ranges in homozygotes and compound heterozygotes for the 35delG, W77R, and V37I mutations. Spiess et al [2002] found that uncoupling gap junctions in the Mongolian gerbil inner ear leads to large decreases in OAE magnitudes, but the OAEs, particularly in the low frequencies, do not disappear completely. Also, studies of mice lacking connexin 26 in the inner ear epithelial gap junction network suggest that the cochlear hair cells develop normally in utero, then many, but not all, begin to die postnatally [Cohen-Salmon et al, 2002].…”
Section: Discussionmentioning
confidence: 92%
“…In patients with connexin mutations, auditory function tests demonstrate a reduced or absent distortion product of otoacoustic emission (DPOAE; Engel-Yeger et al, 2002. Local cochlear application of gap junctional blockers also causes a large reduction in DPOAE in the gerbil (Spiess et al, 2002). The DPOAE arises from the active cochlear mechanics, contributed mainly by outer hair cell electromotility in mammals (Liberman et al, 2002;Cheatham et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Yet this need not promote overt strial pathology. Notably, mitochondrial inhibitors applied in guinea pigs reproduce many of the features of noise injury (Hoya et al 2004;Okamoto et al 2005), while gap junction inhibitors only somewhat reproduce the effects of noise (Spiess et al 2002). In any event, the appearance of the lateral wall does not readily indicate which cells or genes may drive phenotypic differences.…”
Section: Genes and Processes That Establish Or Modulate The Epmentioning
confidence: 97%